Design de novos derivados da ftalocianina de zinco para emprego em óptica não-linear - Araújo, Diesley Martins da Silva (2012)
The present study aims the proposition, by "Molecular Engineering", of derivatives of Zinc Phthalocyanine with desirable characteristics for application in photonic technologies. To characterize these compounds, it was employed a theoretical study, including electronic structure, geometry, energy states, electronic transitions, photophysical and some nonlinear optical (NLO) properties. The three derivatives under study were proposed to introduce peripheral groups in Zinc Phthalocyanine to encompass a range of different "push-pull" groups. The first compound, α-diethylamino-β-nitro-zinc phthalocyanine (1), has in its structure sterically smaller groups which possess relatively moderate electronic delocalization. In the second compound, β-(n-butoxy)-nitrophenylethynyl-zinc phthalocyanine (2), were inserted large groups with high capability to promote the electron delocalization in the macrocycle. Finally, the third, α-β-sulfonyl-ammonium zinc phthalocyanine (3), charged substituents were inserted as peripheral groups, which give to the molecule a high possibility of polarization. The study revealed that there is a greater participation of the HOMO and LUMO orbitals in the first electronic transition, and that these orbitals exhibit a delocalization of electron density from the donor to acceptor groups. The compound (2) presented a red shifted transition (μMAX= 744 nm) when compared to the other two, evidencing an effective participation of the added substituents in the process of electronic delocalization. For all derivatives, the dipole moment estimated for the first excited state was higher than the value presented by these compounds in the ground state. The derivative (2) presented the highest change, with a value of μS1 about 6% larger than μS0. Among the nonlinear optical parameters, the derivative (3) presented the smallest values of polarizability (α) and first hyperpolarizability (β), in despite of having the highest values of dipole moment. The results obtained points that derivative (2) displays promising properties for application in NLO. However, future studies may reveal more precisely what is the real applicability of that derived in photonic technologies.